Evaluasi Sikap Berdemokrasi Mahasiswa Ditinjau dari Berpikir Kritis dan Model Pembelajaran Group Investigation pada Mata Kuliah Kewarganegaraan - Muhammad Nurman (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
Students' democratic attitudes are influenced by the application of the group investigation learning model and students' critical thinking skills. This study aims to evaluate students' democratic attitudes after learning using the group investigation learning model, and the interaction of the group investigation learning model and critical thinking on students' democratic attitudes. The target population in this study were all students of the Elementary Madrasah Teacher Study Program, Faculty of Tarbiyah and Teacher Training, State Islamic University of Mataram, while the accessible population were students of the Elementary Madrasah Teacher Study Program Semester I, Academic Year 2025/2026. Sampling was done randomly, this was done because the number of semesters I of the Elementary Madrasah Teacher Study Program consists of six classes and each class consists of 30 students. Then, four classes were taken to be used as research samples, namely two classes as experimental classes and two classes as control classes. Based on the results of random sampling, it was found that IB, ID as experimental classes and IA, IE as control classes. The design of this study used a treatment by level 2 x 2 design. The independent variables consisted of the group investigation and conventional learning models (A). The independent variable attributes are classified into 2: high critical thinking and low critical thinking (B). The research hypothesis was tested using a two-way 2 x 2 analysis of variance (ANOVA) and continued with the Dunnet t test. The results of the study showed that (1) The democratic attitudes of students who learned using the group investigation learning model were higher than those who learned using the conventional learning model, (2) There was an interaction between the learning model and critical thinking skills on students' democratic attitudes.